Design and analysis of composite structures : with applications to aerospace structures - 497607 Kassapoglou, Christos (Reston, Va. : American Institute of Aeronautics and Astronautics ; United Kingdom : b John Wiley & Sons, 2010)
Includes bibliographical references and index.